KOMITMEN GURU DITINJAU DARI MOTIVASI BERPRESTASI DAN PEGAWASAN KEPALA SEKOLAH PADA SD NEGERI 04 NANGGALTARUSANKABUPATEN PESISIR SELATAN - Ermaida Ermaida (Program Studi PGSD FKIP Universitas Bung Hatta, 2020)
Teachers who have seriousness in carrying out their duties will always be responsible, have a high level of care for their duties, tend to be disciplined, and have concern for the advancement of education and direct superiors are the characteristics of a teacher who has a commitment to competence. Teachers who are committed to providing a lot of time to carry out tasks related to learning such as: designing learning, managing learning and always thinking about ways to improve the active learning achievement of students. The oversight function will be carried out in accordance with the rules if the supervisor can formulate a comprehensive, sustainable, planned and systematic program. Supervisors must be able to carry out curriculum development, organize teaching and learning processes and broaden the experience of teachers and bring corrective actions